Antimicrobial Resistance in Enterobacterales and Its Contribution to Sepsis in Sub-saharan Africa - Tompkins, Kathleen; Juliano, Jonathan J.; van Duin, David (Frontiers in Medicine, 2021)
Antibiotic resistant Enterobacterales are a growing threat to Sub-Saharan Africa. Genes causing antibiotic resistance are easily spread between the environment and humans and infections due to drug resistant organisms contribute to sepsis mortality via delayed time to appropriate antimicrobial therapy. Additionally, second- or third-line antibiotics are often not available or are prohibitively expensive in resource-constrained settings leading to limited treatment options. Lack of access to water and sanitation facilities, unregulated use of antibiotics, and malnutrition are contributors to high rates of antibiotic resistance in the region. Improvements in the monitoring of drug resistant infections and antibiotic stewardship are needed to preserve the efficacy of antibiotics for the future.